(untitled) (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2020)
Today, the problem of the implementation of the inclusive education, preparing the teacher to work with students with special educational needs (with SEN) is urgent. The use of probabilistic and mathematical statistics in distance learning technologies in the teaching contributes to the self-presentation of students with SEN and gives them more opportunities for quality education. The distance learning technologies can become indispensable for SEN students. However, the methodology for using ICT for their learning is not well established and needs further research and validation. Additional teacher training is needed to teach students with inclusion. Purpose of the article: Because of the analysis of theoretical sources and practical experience, to highlight some aspects of the methodology of teaching mathematics to students with special educational needs using ICT, methodological training of mathematics teachers. The features of the use of the developed interactive exercises LearningApps and GeoGebra in teaching stochastics of students with SEN, in particular with hearing impairments, are presented. Application of forms of collaboration through the network is considered, possibilities of using the method of educational projects as possible directions of socialization are described. The conclusions are made about the expediency of using students learning with SEN online services LearningApps, GeoGebra, implementation of the method of educational projects. A tutorial on mathematics teaching methodology is presented, which should be used in the preparation and advanced training of teachers. Successful implementation of the developed system of tasks, selected tools and forms of work requires the additional development of instructional and methodological materials for the assistant teacher (assistant), that is essential for the successful implementation of the Concept of inclusive education. In the future, it is expedient to expand the study of the possibility of using blended learning for the development of cognitive, creative, communicative, and collaborative skills, which are the basic competences of the 21st century for students with SEN.